Soluble urokinase plasminogen activator receptor predicts mortality in patients with systemic inflammatory response syndrome. (8th April 2014) - Raggam, R. B.; Wagner, J.; Prüller, F.; Grisold, A.; Leitner, E.; Zollner‐Schwetz, I.; Valentin, T.; Krause, R.; Hoenigl, M.
Abstract Objective The soluble urokinase plasminogen activator receptor (suPAR) reflects inflammation. However, the prognostic value of suPAR measurements, particularly at the very early onset of systemic inflammatory response syndrome (SIRS), is less well defined. Methods The prognostic potential of suPAR levels in patients with SIRS was evaluated. From November 2010 until April 2013, 902 adult patients presenting with SIRS were investigated. Blood samples for laboratory testing of inflammation markers were collected simultaneously with initial blood cultures. suPAR testing was performed using suPARnostic© assay. Results Analyses of receiver operating characteristics curves revealed areas under the curve (AUCs) of 0.818 for predicting overall mortality within 48 h (36/902 patients died), 0.739 for 30‐day mortality (117/902 died) and 0.706 for predicting 90‐day mortality (151/902 died). AUCs for procalcitonin (0.777, 0.671 and 0.638), interleukin‐6 (0.709, 0.593 and 0.569) and C‐reactive protein (0.66, 0.594 and 0.586) as well as renal function and age were markedly lower. Using multivariable regression analyses, suPAR levels (P < 0.001) remained significant predictors of 48‐h mortality, whereas suPAR levels (P < 0.001) and bacteraemia (P = 0.002 and P = 0.001, respectively) remained significant predictors of 30‐ and 90‐day mortality. Using Kaplan–Meier survival plots, patients with suPAR <9.15 ng mL−1 at SIRS onset had a clear benefit. Conclusion suPAR plasma level determined at early SIRS is predictive for mortality.